Crystal structure of a DNA decamer showing a novel pseudo four-way helix-helix junction. - Spink, N (1995)
The crystal structure of the decanucleotide d(CGCAATTGCG)2 has been solved by a combination of molecular replacement and heavy-atom procedures and has been refined to an R factor of 20.2% at 2.7 A. It is not a fully base-paired duplex but has a central core of eight Watson-Crick base pairs flanked by unpaired terminal guanosines and cytosines. These participate in hydrogen-bonding arrangements with adjacent decamer duplexes in the crystal lattice. The unpaired guanosines are bound in the G+C regions of duplex minor grooves. The cytosines have relatively high mobility, even though they are constrained to be in one region where they are involved in base-paired triplets with G.C base pairs. The 5'-AATT sequence in the duplex region has a narrow minor groove, providing further confirmation of the sequence-dependent nature of groove width.